HUMAN RESOURCE IMPROVEMENT EFFORTS: EXPLORING THE ROLE OF COMMUNICATION SKILLS AND STRUCTURALISM IN JOB INTERVIEW SUCCESS - Nugraha, Roni Setia; Fadlilani, Lailanisa; Renaldo, Zainal Arifin (Universitas Nusa Cendana, 2025)
This study explores the influence of effective communication and structuralism on the readiness of Politeknik Caltex Riau (PCR) students in job interviews. While students excel in technical skills, they often struggle with verbal and non-verbal communication during interviews. Utilizing surveys and interviews with 184 final-year students, the research reveals that effective communication has no significant impact on job interview readiness, while structural factors such as social norms and cultural adaptation significantly affect preparedness. The results indicate that the combination of these factors accounts for 57.8% of students' readiness. This finding suggests that enhancing communication training and understanding of structural frameworks could improve students' job interview outcomes. The study provides valuable insights for curriculum development aimed at increasing employability skills for future graduates in a competitive job market. Keywords: Effective Communication; Structuralism; Job Interview; Human Resource Development